2016
DOI: 10.1007/s10903-016-0345-y
|View full text |Cite
|
Sign up to set email alerts
|

The Catalonian Expert Patient Programme for Chagas Disease: An Approach to Comprehensive Care Involving Affected Individuals

Abstract: The Catalonian Expert Patient Programme on Chagas disease is a initiative, which is part of the Chronic Disease Programme. It aims to boost responsibility of patients for their own health and to promote self-care. The programme is based on nine sessions conducted by an expert patient. Evaluation was focusing in: habits and lifestyle/self-care, knowledge of disease, perception of health, self-esteem, participant satisfaction, and compliance with medical follow-up visits. Eighteen participants initiated the prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 6 publications
0
24
0
6
Order By: Relevance
“…We observed a larger percentage of women participating in all of the interventions conducted. Other publications had already shown that there was more participation among women than men, both in the awareness events and in their interest and need to perform the screening in relation to Chagas [24,27,28]. According to previous studies, women show more concern and interest in screening, mainly because of feelings of guilt, worry, and responsibility for the potential transmission of the disease to their children [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed a larger percentage of women participating in all of the interventions conducted. Other publications had already shown that there was more participation among women than men, both in the awareness events and in their interest and need to perform the screening in relation to Chagas [24,27,28]. According to previous studies, women show more concern and interest in screening, mainly because of feelings of guilt, worry, and responsibility for the potential transmission of the disease to their children [5].…”
Section: Discussionmentioning
confidence: 99%
“…In Catalonia in 2011 the ICS [24] implemented the "Expert Patient in Chagas Disease Program" with the support of the WHO. The methodology that was followed in the sessions was established in the protocol of the "Expert Patient Program" [25], which has been used for other diseases and was adapted to the distinct features that CHD has.…”
Section: Construction Process Of the Community Strategies (2004-2013)mentioning
confidence: 99%
“…These patients must be monitored by a multidisciplinary team with the presence of a psychologist and social worker. The creation of associations of people with CD in communities and initiatives such as The Catalonian Expert Patient Program on Chagas Disease should be adopted to increase patients' knowledge about the disease, provide social and emotional support to patients, and promote self-care [25,48].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, CD shows complex interactions and dependencies: It is not possible to treat with infestation rates >3% and the lack of perceived effective antiparasitic and symptomatic treatment options undermines the motivation for primary and secondary prevention. Holistic approaches against NTDs [ 57 ] and community/patient empowerment [ 58 , 59 ] could help to overcome those structural barriers.…”
Section: Discussionmentioning
confidence: 99%